2008
DOI: 10.1021/ma702136k
|View full text |Cite
|
Sign up to set email alerts
|

Studying a Slow Polymerization:  A Kinetic Investigation of the Living Anionic Polymerization of PC Bonds

Abstract: The n-butyllithium-initiated living anionic polymerization of MesPdCPh 2 (Mes ) 2,4,6trimethylphenyl) was studied at a variety of temperatures (T ) 296. 3, 301.8, 307.4, 313.0, 318.6, and 324.2 K) with a fixed monomer-to-initiator ratio (50:1). The consumption of monomer and formation of polymer n Bu[MesP-CPh 2 ] n Li was monitored by 31 P NMR spectroscopy, and the conversion data obtained were analyzed using first-order kinetics. Up to 50% conversion, the plot of ln [M] 0 /[M] vs time was linear, and appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…15 In contrast, the anionic polymerisation of MesP]CPh 2 can be performed in a "living" fashion and provides access to block copolymers that selfassemble in block selective solvents. [16][17][18] The versatile chemical functionality of the P(III) moiety within PMPs, which can be oxidised to P(V) or coordinated to metals or Lewis acids, is of considerable interest. 19,20 Molecular phosphines bearing p-conjugated chromophores are widely used as uorescent probes since they exhibit "turn-on" emission upon oxidation or coordination.…”
Section: Introductionmentioning
confidence: 99%
“…15 In contrast, the anionic polymerisation of MesP]CPh 2 can be performed in a "living" fashion and provides access to block copolymers that selfassemble in block selective solvents. [16][17][18] The versatile chemical functionality of the P(III) moiety within PMPs, which can be oxidised to P(V) or coordinated to metals or Lewis acids, is of considerable interest. 19,20 Molecular phosphines bearing p-conjugated chromophores are widely used as uorescent probes since they exhibit "turn-on" emission upon oxidation or coordination.…”
Section: Introductionmentioning
confidence: 99%
“…Upon treatment of a THF solution of 3 with [(tht)AuCl] (1 equiv, tht = tetrahydrothiophene), a small shift relative to 3 was observed in the 31 P NMR spectrum (d = À36.4 ppm versus d = À37.3 ppm in THF). A signal was detected in the 13 C NMR spectrum (d = 175.2 ppm), which is similar to 3·(AuCl) 2 (d = 177.6 ppm; IMes·AuCl d = 173.4 ppm). [26] Although this species was not isolated, the chemical shifts suggest that complexation to gold occurs first at the carbene center.…”
mentioning
confidence: 92%
“…P = C bonds have been polymerized successfully using radical or anionic initiators. [13] The potential cationic polymerization of P=C bonds is particularly intriguing owing to the putative involvement of a phosphenium cation (R 2 P + ) as the propagating species. [14] We have previously reported that treating tBuP = CHtBu (2 equiv) with trifluoromethanesulfonic acid affords an asymmetric diphosphiranium cation containing a P 2 C heterocycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent analysis of the solution of the crude reaction mixture in THF by 31 P NMR spectroscopy showed signals that can be assigned to monomer (d = 233) and polymer (d = À10) in ratios that suggested approximately 41 % conversion [16] to poly(methylenephosphine). After precipitation from the THF solution with hexanes ( 3), polymer free of monomer 1 was isolated in 10 % yield [gel-permeation chromatography (GPC) with light scattering: M n = 10 000 g mol À1 , polydispersity index (PDI) = 1.3].…”
mentioning
confidence: 99%